RELIGIOUS KNOWLEDGE AND PRACTICES AMONG MALAYSIAN ABORIGINES: A PRELIMINARY STUDY - Ramlan Mustapha,; Nazatul Akmar Mokhtar,; Asmadi Abdul Rahman,; Sh Mohd Firdaus Sh Othman,; Halim Ismail,; Fahmi Zaidi Abdul Razak, (Journal of Islamic, Social, Economics and Development, 2023)
The indigenous people residing in the state of Pahang possess great potential for advancement in religious knowledge and practice. However, limited studies have been conducted to assess the mastery of Fardhu Ain (basic religious obligations) and Al-Quran recitation among this population. This quantitative study aims to identify the level of mastery of Fardhu Ain and recitation of the Qur'an within the indigenous community. A questionnaire and a Fardhu Ain practice test, as well as an Al-Quran recitation test, developed by educators, were utilized as research instruments. The study involved 250 participants. The findings reveal that a majority of the indigenous community demonstrate mastery of Fardhu Ain, but the level of proficiency in reciting the Qur'an remains low. These results shed light on the existing gaps and emphasize the importance of targeted interventions to enhance Qur'an recitation skills among the indigenous population in Pahang.